PEDAGOGY OF COOPERATION IN THE EDUCATIONAL PROCESS – MODERN PERSONALITY-ORIENTED TECHNOLOGIES (Scientific journal of the Fergana State University, 2024)
Reliance on pedagogy focused on direct cooperation in the educational process is the application of modern technologies of personally-oriented learning throughout the activity, collectivity, focused on working together in a modern environment, fostering in the learner a sense of full pride in the mental and moral qualities of peers, pride in his worthy place in the team, accustoming him to active learning together with members of the team. This article considers pedagogy oriented to cooperation in the educational process - modern technologies of personality-oriented learning.